2013
DOI: 10.1161/circresaha.112.300849
|View full text |Cite
|
Sign up to set email alerts
|

Novel Long Noncoding RNAs Are Regulated by Angiotensin II in Vascular Smooth Muscle Cells

Abstract: Rationale Misregulation of angiotensin II (Ang II) actions can lead to atherosclerosis and hypertension. Evaluating transcriptomic responses to Ang II in vascular smooth muscle cells (VSMCs) is important to understand the gene networks regulated by Ang II which might uncover previously unidentified mechanisms and new therapeutic targets. Objective To identify all transcripts, including novel protein-coding and long non-coding RNAs, differentially expressed in response to Ang II in rat VSMCs using transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
212
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(220 citation statements)
references
References 59 publications
2
212
0
2
Order By: Relevance
“…ChIP-seq-ChIP experiments were performed with an antihistone H3 lysine 4 monomethylation (H3K4me1) antibody (Abcam, ab8895) using standard ChIP and our published protocols (21). Sequencing libraries compatible with Illumina HiSeq 2500 technology were generated using Illumina protocols.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP-seq-ChIP experiments were performed with an antihistone H3 lysine 4 monomethylation (H3K4me1) antibody (Abcam, ab8895) using standard ChIP and our published protocols (21). Sequencing libraries compatible with Illumina HiSeq 2500 technology were generated using Illumina protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Leung et al 62) identified a lncRNA in the angiotensin-induced SMCs and termed it lnc-Ang362. They found that lnc-Ang362 knockdown decreased the proliferation of SMCs and further confirmed that lnc-Ang362 was proximal to miR-221 and miR-222 and obviously attenuated the expression of the two miRNAs.…”
Section: Long Noncoding Rnas In Smcsmentioning
confidence: 99%
“…For example, it was reported that angiotensin II induced the expression of lncRNAs in vascular smooth muscle cells. 11 Another study documented dysregulated lncRNAs in infarcted mouse hearts. 12 Interestingly, Yang et al, 13 performed RNA deep sequencing and they identified HF associated lncRNAs in human patients.…”
Section: Introductionmentioning
confidence: 99%